1987
DOI: 10.1021/bi00400a007
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-induced asymmetry between active sites of cytoplasmic malate dehydrogenase: a chemical modification study

Abstract: The iodoacetate-dependent and iodoacetamide-dependent inhibition of cytoplasmic malate dehydrogenase (s-MDH) has been examined. We have confirmed previous reports that iodoacetate inhibits this dimeric enzyme by modifying a single active site methionine per s-MDH subunit. Time courses for the inactivation of the solution-state enzyme with both reagents indicate each s-MDH subunit is modified with equal rapidity in the absence of substrate or cofactor. However, the subunits react with distinctly different rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…CCB, for example, is known to act as an inhibitor of microtubule formation as well as a glucose transport inhibitor. 25 It is also pertinent to note that IOA can inhibit malate dehydrogenase, 46 which would consequently inhibit oxidative reactions fueled by glutamine. In the case of IOA, any remaining MTTreducing activity would therefore have to be generated by nonoxidative and nonglycolytic pathways.…”
Section: Iovsmentioning
confidence: 99%
“…CCB, for example, is known to act as an inhibitor of microtubule formation as well as a glucose transport inhibitor. 25 It is also pertinent to note that IOA can inhibit malate dehydrogenase, 46 which would consequently inhibit oxidative reactions fueled by glutamine. In the case of IOA, any remaining MTTreducing activity would therefore have to be generated by nonoxidative and nonglycolytic pathways.…”
Section: Iovsmentioning
confidence: 99%
“…Detailed kinetic studies were also performed on sMDH preparations that were partially inhibited by iodoacetate, a reagent which binds covalently to the enzyme's active site (Zimmerle et al, 1987). Representative results are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, previous studies from this laboratory have shown that under standard assay conditions, all active sites of the sMDH preparation are identical by the criterion of reactivity toward the active-site-specific reagent, iodoacetic acid. This reagent specifically modifies Met 98 of the enzyme's active site in a reaction whose rate is sensitive to changes in the active-site environment (Zimmerle & Alter, 1983;Zimmerle et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be noted that, in the absence of ligands, the subunits forming the MDG molecule are chemically identical and are arranged symmetrically [22,23]. However, the bonding of a ligand to one of the subunits of the enzyme can cause an asymmetry in the arrangement of the functional groups belonging to the neighboring subunits [33] and influence the access to the unoccupied sites of bonding.…”
mentioning
confidence: 99%